Investigation of wavelength and bandwidth as interrogation parameters in an FBG based optical NDT system - Leo, Catherine Wan Ting. (2009)
The report focuses on the use of FBG sensors on composites and composite honeycomb structures to investigate and analyse the feasibility of using wavelength and bandwidth as interrogation parameters in a temperature experiment and three-point bending test, as well as look into the feasibility of using FBG sensors to carry out vibration testing.